1991
DOI: 10.1200/jco.1991.9.1.7
|View full text |Cite
|
Sign up to set email alerts
|

How American oncologists treat breast cancer: an assessment of the influence of clinical trials.

Abstract: The present study was designed to assess the preferred methods of treatment of breast cancer by American oncologists, and the impact of clinical trials on their practice. We mailed 465 questionnaires to surgical, radiation, or medical oncologists. The questionnaire described five hypothetic patients with breast cancer, and respondents were asked to select their preferred treatment for each patient. For primary breast cancer, most physicians would offer the choice of local excision followed by radiation therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
3

Year Published

1991
1991
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 0 publications
3
14
0
3
Order By: Relevance
“…It appeared that initial training had a greater influence in determining the practice of physicians than the emerging empirical evidence from clinical trials. This is consistent with studies that have investigated the influence of empirical evidence on clinical practice for the management of breast cancer patients [3]. It was found that the results of large randomized clinical trials had minimal impact on the practice of American surgical, medical and radiation oncologists if the results opposed the individual physicians' preferences and beliefs in the value of the given treatment [3].…”
Section: Resultssupporting
confidence: 76%
“…It appeared that initial training had a greater influence in determining the practice of physicians than the emerging empirical evidence from clinical trials. This is consistent with studies that have investigated the influence of empirical evidence on clinical practice for the management of breast cancer patients [3]. It was found that the results of large randomized clinical trials had minimal impact on the practice of American surgical, medical and radiation oncologists if the results opposed the individual physicians' preferences and beliefs in the value of the given treatment [3].…”
Section: Resultssupporting
confidence: 76%
“…Furthermore, in line with our results on an observational study, many Bayesian re-analyses of clinical trials concluded that the observed differences were not likely to be true [42,43]; the other way round, the clinical community seems to decline results of clinical trials that counteract strong prior beliefs [44,45]. Despite this, health professionals are still reluctant to adopt the Bayesian approach [20], at least as a complementary method to further validate their studies.…”
Section: Discussionsupporting
confidence: 71%
“…In contrast to the magnitude of this problem rather few' prospective studies have been published analyzing both the degree and the duration of response [5]. From a recently published questionnaire analysis it was concluded that the value of short-term low'-dose irradiation for patients w'ith painful bone metastases is underestimated at least in the United States [1], The evaluation of pain relief makes a prospective study design mandatory. As controlled trials are difficult to perform in a patient population treated w'ith a palliative aim, prospective follow'-up studies involving a well-defined group of patients are important to w'ork out a more individualized approach.…”
Section: Introductionmentioning
confidence: 99%